An iridium–SPO complex as bifunctional catalyst for the highly selective hydrogenation of aldehydes. Issue 1 (27th November 2017) - Cano, Israel; Martínez-Prieto, Luis M.; Vendier, Laure; van Leeuwen, Piet W. N. M.
Abstract : An Ir(iii ) hydride catalytic system shows very high activities and selectivities in the chemoselective hydrogenation of various substituted aldehydes. Abstract : A secondary phosphine oxide (SPO) ligand ( tert -butyl(phenyl)phosphine oxide) was employed to generate an Ir–SPO complex which shows a particular ability to activate dihydrogen under mild conditions without the help of an external base or additive. Such an iridium(i ) complex serves as a precursor for homogeneous catalysis since under H2 it is converted to a mixture of several iridium(iii ) hydride species that are the active catalysts. This system was found to be a highly active catalyst for the hydrogenation of substituted aldehydes, giving very high conversions and chemoselectivities for a wide range of substrates. The SPO ligand presumably plays a key role in the catalytic process through heterolytic cleavage of H2 by metal–ligand cooperation. In addition, an exhaustive characterization of the different iridium hydride species was performed by 1D and 2D NMR spectroscopy. The oxidative addition of H2 to the Ir(i )–SPO complex is highly stereoselective, as all generated Ir(iii ) hydrides are homochiral. Finally, the crystal structure, as determined by X-ray diffraction, of a dinuclear iridium(iii ) hydride complex is described.